KAKAWIN BALI DWIPA ANALISIS KONVENSI DAN INOVASI - Budastra, I Gusti Bagus (Humanis; Volume 5. No. 1. Oktober 2013, 2013)
Kakawin is a literary work that is formed by wirama or wirama-wirama and each wirama bound by several conditions, such as wr?tta and matra. Kakawin is one element of culture that has been very important in order to participate to support the promotion and development of regional culture in particular and the national culture generally. Kakawin literary arts in Bali received considerable attention from the public. in some kind of religious ceremony kakawin literary art is used as an accompaniment the ceremony. Also in some kind of classical arts like drama, ballet, puppets and more. Kakawin Dwipa Bali is one of the minor kakawin in Bali. In this study using two theories, namely the convention theory and the theory innovation of kakawin. Convention theory is used to determine the terms of language conventions that provide an understanding of language as a medium used in kakawin, literary conventions which include beauty content and form in kakawin, and cultural conventions covering cultural background of the kakawin.  Innovation theory is used to determine the presence of renewal and change in terms of language, literature and culture in literature kakawin.
Keywords: Kakawin Bali Dwipa, conventions, innovation.